Asuhan Keperawatan Jiwa Pada Tn.M Dengan Masalah Utama Resiko Perilaku Kekerasan Akibat : Skizofrenia Tak Terinci Di Ruang Srikandi RSJD Dr.Amino Gondohutomo Provinsi Jawa Tengah - Fika Putri Utari; Titi Sri Suyanti; Tati Karyawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Mental disorders are a group of symptoms characterized by changes in a person's thoughts, feelings and behavior that cause dysfunction in carrying out daily activities. Within mental disorders there are several diagnoses, one of which is schizophrenia. Schizophrenia is a serious mental disorder characterized by decreased or inability to communicate, cognitive impairment, inability to think abstractly, and experiencing difficulty in carrying out daily activities. Schizophrenia is a mental disorder that is a major problem in countries where schizophrenia is a type of psychosis that ranks at the top of all existing mental disorders. Schizophrenia is part of a mental disorder characterized by strange behavioral and speech deviations, incoherent thoughts, delusions, hallucinations, where this condition occurs due to changes in the physical structure and chemistry of the brain (Tri et al., 2020).